Kajian postmodernisme Jean Francois Lyotard dalam novel Dompet Ayah Sepatu Ibu karya J.S. Khairen - Wahyuningtias, Nova Hida (Jurnal Pendidik Indonesia, 2025)
This study aims to describe the postmodern aspects in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen based on Jean-François Lyotard's theory of postmodernism. As a cultural product, literature constantly evolves in response to changes in time and social reality. In this context, a new paradigm emerged to replace modernism—postmodernism—which has influenced the form, content, and modes of literary expression. This research employs a qualitative descriptive approach with data sourced from the novel's text that represents postmodern elements such as eclecticism, parody, pastiche, irony, and camp. The findings reveal that the novel reflects the characteristics of postmodern society through the actions and attitudes of its characters in facing the realities of their time. Key findings include the psychological exploration of the main characters—Zenna and Asyrul—as well as creative artistic expressions that do not fully represent reality objectively. Eclecticism is evident in the integration of foreign cultures into local culture; parody appears through emotionally dramatized narratives; pastiche is present in the imitation of styles and themes from past texts, such as depictions of a humble family struggling against poverty and ignorance; while irony highlights the contrast between the characters' expectations and the reality they must face. Thus, this novel presents a strong representation of complex and reflective postmodern values.